Streptococcal toxic shock syndrome caused by β-hemolytic streptococci: Clinical features and cytokine and chemokine analyses of 15 cases. Issue 5 (May 2019) - Yoshizawa, Sadako; Matsumura, Takayuki; Ikebe, Tadayoshi; Ichibayashi, Ryo; Fukui, Yuto; Satoh, Takahiro; Tsubota, Takaya; Honda, Mitsuru; Ishii, Yoshikazu; Tateda, Kazuhiro; Ato, Manabu
Abstract: Objectives: β-Hemolytic streptococci occasionally cause severe infections such as necrotizing fasciitis and streptococcal toxic shock syndrome (STSS). Here, we conducted a prospective study to investigate the production of cytokines and chemokines in patients with STSS to explore its pathogenesis in survivors and fatal cases. Methods: From January 2013 through August 2015, all culture results from normally sterile sites were prospectively followed and screened for STSS. Clinical characteristics of the patients with STSS were evaluated and compared between survivors and fatal cases. Serum samples were collected on admission for quantification of various cytokines and chemokines. Bacterial strains were categorized by Lancefield grouping and analyzed for the emm type, and presence of speA, speB, speC, and speF . Results: Fifteen patients received diagnosis of STSS. The median age of the patients was 60-year-old, and the mortality rate was 40% despite intensive treatment. Nine strains were categorized as group A, two belonged to group G, and four to group B. Group A contained various emm genotypes. Unexpectedly, potent proinflammatory cytokine levels such as TNF-α and IL-1β were not significantly elevated, and comparison with surviving patients showed that IL-6, IL-8, and MCP-1 levels were significantly decreased and creatine kinase level was significantly elevated in fatally ill cases. Conclusion: Our results indicate that reduced production of proinflammatory cytokines and chemokines may be involved in STSS pathogenesis and critical for prognosis of patients with STSS.